Pengaruh Kemandirian, Motivasi, Dan Pengetahuan Kewirausahaan Berbasis Syariah Terhadap Minat Memulai Usaha Pada Mahasiswa FEBI UIN STS Jambi - Tetti Pebrianti; Suhar AM; Dessy Anggraini (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This study aims to determine the effect of independence, motivation, and knowledge of sharia-based entrepreneurship on the interest in starting a business in students of the Faculty of Economics and Islamic Business, Sulthan Thaha Saifuddin Jambi State Islamic University. Primary data collection method used is to use a media questionnaire. The sample for this research was students of the Faculty of Economics and Islamic Business, Sultha Thaha Saifuddin Jambi State Islamic University, Jambi, Class of 2019-2021, totaling 100 respondents. This research method is quantitative with multiple linear regression analysis as its analysis. The research results show that independence (X1) has no significant negative effect on the intention to start a business (Y). The results of this study can be seen that the value of tcount (1.640) < ttable (1.985) with a significance value of 0.104 > 0.05 which means Ha is rejected and Ho is accepted. Motivation (X2) shows that there is a positive and significant influence on the interest in starting a business (Y). The results of this study can be seen that the value of tcount (2.389)>ttable (1.985) with a significance value of 0.019 <0.05, which means that Ha is accepted and Ho is rejected, and entrepreneurial knowledge (X3) shows that there is a positive and significant influence on the interest in starting effort (Y). The results of this study can be seen that the tcount (2.389) > ttable (1.985) with a significance value of 0.019 <0.05, which means that Ha is accepted and Ho is rejected. Based on the results of the F test, the Fcount value is 106.534 and Ftable is 2. 70 (106.534 > 2.70), and a significant value of 0.000 where p <0.05 so the F test result is 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected, which means there is a significant influence between the variables. Independence, Motivation and Knowledge of Entrepreneurship simultaneously on the variable Interest in Entrepreneurship.